Low Serum Testosterone Level and Its Relationship with Hypogonadism in Patients with Chronic Liver Disease - Waqar Zafar, Farah Naz Tahir, Hooria Bakhtawar, Muhammad Abdullah, Mahboob Qadir, Misbah Iqbal Hanif, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Loss of libido, low serum testosterone levels, and other symptoms of hypogonadism like subfertility, gynecomastia, and immature testes, is a prevalent medical condition amongst males with advanced chronic liver disease. The purpose of this investigation was to evaluate the low serum testosterone levels association with hypogonadism in people with chronic liver disease. Study Duration: This study was carried out at Outpatient Department (OPD) of Medicine Ayub Teaching Hospital, Abbottabad from 1st January 2022 to 30th June 2022. Material and Methods: The retrospective study was completed on two hundred confirmed patients of hypogonadism with liver cirrhosis. In the repository, the available data was divided into two groups. The first group of chronic liver disease patients was diagnosed due to non-alcoholic fatty liver disease (NAFLD) and second patient group due to alcoholic liver disease (ALD). The patient in NAFLD group were in the age group between 15-30 years whereas the patients from ALD group were 30-60 years of age. The diagnostic values of total testosterone and Sex hormone binding globulin (SHBG) were collected from patient’s record. The independent t test was used for statistical analysis by using SPSS version 22. The frequency distribution of testosterone was also calculated between two types of chronic liver disease patients. Results: The retrospective research was performed. The data were dispersed across two age groups. The youth had no alcohol-related data, while the elderly had. According to hospital data, distribution was based on age between 15 and 30 years (NAFLD) and between 30 and 60 years (ALD). When T-test was applied it showed that there was no statistically significant difference found in means of SHBG between two age groups amongst chronic liver disease patients. In the case of serum testosterone, there was a statistically significant (p 0.05) difference between age groups (Table 1). Figures 1 and 2 illustrate the frequency distribution of total testosterone and its comparison within the liver cirrhosis group, respectively. Practical Implication: Our study predicted that low testosterone can raise the risk of mortality, the necessity for liver transplantation, and the likelihood of severe infection in men with cirrhosis given the mechanisms of action of testosterone. Conclusion: On the basis of two groups of liver cirrhosis, there is a significant age-related change in total serum testosterone, its control by the pituitary and it’s binding to SHBG in males over the age of forty. However, no substantial data was discovered in sex hormone binding globulin. Low testosterone levels are associated with hypogonadism in patients with cirrhosis of the liver. The effect of testosterone replacement treatment on increasing muscle quality in male cirrhotic patients remains to be determined. Safety and effectiveness of the treatment requires additional prospective research. Keywords: Sex Hormone Binding Globulin, Serum Testosterone, Hypogonadism, Chronic Liver Disease